Entre dois países, sonhos e ilusões: trajetórias de e/imigrantes bolivianos em São Paulo (1980-2000) - Fernandez, Camila Collpy Gonzalez (2016)
The present investigation approaches the trajectories of Bolivian e/immigrants in São Paulo within the period of 1980 to 2000 and finds support in the social and cultural History studies to bring contributions regarding these flows. Be means of the life histories of Bolivians established in São Paulo, their expectations, dreams, strategies, networks and processes of insertion in the society of São Paulo, the relations and tensions present in these e/immigrants' everyday lives, often undocumented, are unveiled. Multiple experiences were reported in the statements, enabling to discuss the cultural traces and the identities recreated in this process, besides the marks left not only in the protagonists, but also in the space and in the history of the city of São Paulo. Thus, upon analysis of events organized and/or attended by Bolivians (religious, sport or celebrations), we seek to discuss the perspectives and tensions: acceptance in the reception society, negative stereotypes and search for social and economic recognition inside and outside the network. This way, praying, celebrating and expressing joy are observed as strategic to break negative images regarding the group, focused on the exploration of labor in the sewing business